(untitled) (Journal of Informatics Education and Research, 2025)
Intellectual Property Rights (IPRs) are key drivers of innovation, economic development, and competitive advantage, especially in technology-driven sectors. Tamil Nadu, with its robust industrial base and emerging innovation ecosystems, is strategically positioned to leverage IPR for development. This paper provides a detailed survey of how IPR influences technology transfer, new venture creation, and economic growth in Tamil Nadu. Drawing from global literature, national policies, and regional data, we identify current challenges and opportunities within the IPR framework. The study emphasizes policy gaps, institutional weaknesses, and limited awareness among entrepreneurs and researchers. Recommendations include policy integration, legal reforms, and innovation ecosystem strengthening to optimize the role of IPR in Tamil Nadu’s development.